Cost of coronary syndrome treated with percutaneous coronary intervention and 30‐day unplanned readmission in the United States. Issue 1 (26th December 2019) - Kwok, Chun Shing; Amin, Amit P.; Shah, Binita; Kinnaird, Tim; Alkutshan, Raed; Balghith, Muhammad; Ratib, Karim; Nolan, James; Bagur, Rodrigo; Mamas, Mamas A.
Abstract: Objectives: This study aimed to examine the cost of coronary syndrome treated with percutaneous coronary intervention (PCI) and 30‐day unplanned readmissions. Background: There is limited understanding of the hospital cost of index PCI and 30‐day unplanned readmissions. Methods: Patients undergoing PCI between 2010 and 2014 in the U.S. Nationwide Readmission Database were included. The primary outcome was total cost defined by cost of index PCI and first unplanned readmission within 30 days. Results: This analysis included 2, 294, 244 patients who underwent PCI, and the mean cost was 23, 541 ± 20, 730 ( 10.8 billion/year). There was a modest increase in cost over the study years of 17.5%. Of the 9.4% with an unplanned readmission within 30 days, the mean total cost was 35, 333 ± 24, 230 versus 22, 323 ± 19, 941 for those not readmitted. The variables most strongly associated with the highest quartile of cost were heart failure (adjusted odds ratio (aOR) 25.60 [95% CI 21.59–30.35]), need for circulatory support (aOR 11.62 [10.13–13.32]), periprocedural coronary artery bypass graft (CABG, aOR 585.08 [357.85–956.58]), and readmission within 30 days (aOR 24.49 [22.40–26.77]). An acute kidney injury (AKI; 8.5%), major bleed (0.8%), vascular injury (0.8%), or need for periprodedural CABG (1.4%) had an average increased cost of 21, 935; 30, 898; 27, 875; and 43, 005, respectively, compared to PCI without adverse outcome. Conclusions: The annual 30‐day hospital cost of PCI is approximately 10.8 billion, and the costs associated with in‐hospital adverse events, particularly the need for AKI and periprocedural CABG, were significant.